Copper removal and recovery from copper-containing wastewater by unseeded fluidized-bed process - Capito, Jenelyn A. (College of Engineering, University of the Philippines Diliman, 2015)
Conventional treatment technologies for copper-contaminated effluents suffer from large footprint and high moisture sludge generation. In this study, unseeded fluidized-bed process was applied to remove and recover copper from copper-Containing solutions. The effects of influent copper concentration, precipitant-to-copper molar ratio, precipitant pH, and influent flow rate on copper removal and recovery were investigated. Copper removal and recovery reached 99% and 95%, respectively when the influent copper concentration, precipitant-to-copper molar rati0, precipitant pH, and influent flow rate were 191 mg/L, 2.0-3.0, 9.5 and 35 mL/min, respectively. The effects of EDTA and CH20, components of electroless copper plating solution and rinse water, on copper removal and recovery were also investigated. Results showed that copper removal reached 93% when EDTA concentration was reduced by 1/8 and more than 99% when only copper and CH2O remained in solution. The FTIR spectra of the recovered solids agreed with the absorption bands reported for malachite and azurite minerals. From the solids recovered from the optimum condition, the SEM image displayed an irregular- shaped cluster of small deformed spherical solids and the XRD pattern was consistent with malachite mineral.